2013
DOI: 10.1038/jcbfm.2013.161
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Arterial Bolus Arrival Time is Prolonged in Multiple Sclerosis and Associated with Disability

Abstract: Alterations in the overall cerebral hemodynamics have been reported in multiple sclerosis (MS); however, their cause and significance is unknown. While potential venous causes have been examined, arterial causes have not. In this study, a multiple delay time arterial spin labeling magnetic resonance imaging sequence at 3T was used to quantify the arterial hemodynamic parameter bolus arrival time (BAT) and cerebral blood flow (CBF) in normal-appearing white matter (NAWM) and deep gray matter in 33 controls and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 39 publications
(80 reference statements)
7
53
0
Order By: Relevance
“…However, this is unlikely because none of the eyes had a history of optic neuritis, and the relationship between the retinal blood flow metrics and RNFL thickness was not established. Our findings are compatible with slower blood flow in the cerebral arteries of patients with MS measured by Arterial Spin Labeling Magnetic Resonance Imaging 26 and prolongation of the mean transit time, a measure of the average time contrast takes to transit from the arterial to venous circulation in normal appearing white matter, as described in the dynamic susceptibility contrast MRI study. 6 The retinal hypoperfusion is in alignment with the observation of cerebral hypoperfusion in NAWGM in MS. 27,28 The cerebral hypoperfusion is considered a major step that induces a status defined as energy failure in MS. 29 According to a recent large scale clinical study on 1249 patients, MS lesions tend to occur in areas with lower perfusion.…”
Section: Discussionsupporting
confidence: 88%
“…However, this is unlikely because none of the eyes had a history of optic neuritis, and the relationship between the retinal blood flow metrics and RNFL thickness was not established. Our findings are compatible with slower blood flow in the cerebral arteries of patients with MS measured by Arterial Spin Labeling Magnetic Resonance Imaging 26 and prolongation of the mean transit time, a measure of the average time contrast takes to transit from the arterial to venous circulation in normal appearing white matter, as described in the dynamic susceptibility contrast MRI study. 6 The retinal hypoperfusion is in alignment with the observation of cerebral hypoperfusion in NAWGM in MS. 27,28 The cerebral hypoperfusion is considered a major step that induces a status defined as energy failure in MS. 29 According to a recent large scale clinical study on 1249 patients, MS lesions tend to occur in areas with lower perfusion.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, a reduction of GM CBF measured by ASL was confirmed in all MS patients compared to healthy controls while NAWM CBF has been alternatively found decreased in some studies [9][10][11], or increased in others [12,13]. The reason for the increased NAWM CBF in few studies could be the incomplete separation between NAWM and both WM and enhanced lesions due to the relatively coarse resolution of ASL and non-use of exogenous contrast.…”
mentioning
confidence: 75%
“…Although ASL technique has limitations such as the relatively low spatial resolution and the requirement of a careful position of region of interests to prevent partial volume effects with lesions and blood vessels, it provides a sensitive measure of cerebral perfusion without the need of a contrast since it uses the blood as an endogenous contrast agent [13]. Therefore, ASL might become a useful tool to evaluate experimental neuroprotective drugs in proof-ofconcept studies and reduce both patients' exposure to gadolinium and the costs of clinical trials requesting serial MRIs.…”
Section: Dear Sirsmentioning
confidence: 99%
“…The most obvious potential cause of hypoxia in MS is inadequate vascular perfusion, which does not necessarily imply a reduction in perfusion from normal levels, but several studies have nonetheless revealed cerebral hypoperfusion in MS (recently reviewed in D'Haeseleer et al,22 Juurlink,23 Paling et al24). …”
Section: Discussionmentioning
confidence: 99%